2010
DOI: 10.1111/j.1525-1594.2009.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Pulsatility Effect on the Deformability and Hemolysis of Blood Cells

Abstract: In this study, we investigated the differences between pulsatile cardiopulmonary bypass (CPB) procedure and nonpulsatile CPB procedure in terms of their effects on hemolysis and deformability of red blood cells (RBCs) under various shear stress conditions. In order to research the effects on hemolysis and deformability, four parameters--free hemoglobin (fHb) concentration, normalized index of hemolysis (NIH), deformability index (DI) of RBCs, and elongation index of RBCs--have been deeply investigated. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Cell damage observed even today with prosthetic heart valves, 15,39 cardiopulmonary bypass, 25 and artificial kidneys contributes to anemia, along with the toxic effects associated with free hemoglobin in the circulatory system. 38 The cause of mechanical trauma to blood cells has been attributed to large frictional forces or shear stresses, 30 which are associated with the flow of blood through such devices.…”
Section: Introductionmentioning
confidence: 99%
“…Cell damage observed even today with prosthetic heart valves, 15,39 cardiopulmonary bypass, 25 and artificial kidneys contributes to anemia, along with the toxic effects associated with free hemoglobin in the circulatory system. 38 The cause of mechanical trauma to blood cells has been attributed to large frictional forces or shear stresses, 30 which are associated with the flow of blood through such devices.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies on blood biophysical properties including viscosity, [1][2][3][4][5][6] viscoelasticity, [7][8][9][10][11][12] deformability, [13][14][15][16][17][18] aggregation, [19][20][21][22] and erythrocyte sedimentation rate (ESR), [23][24][25][26][27] various cardiovascular diseases cause changes in the biophysical properties of the blood. The biophysical properties of the blood have been measured to effectively monitor disease states or their progresses.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with the finding by Kang et al, who showed that hemolysis was increased with prolonged CPB duration irrespective of flow condition. 26 …”
Section: Interpretation Of Heterogenous Resultsmentioning
confidence: 97%